Heart Rate Variability in Hyperthyroidism - Kabir, Md Rasel; Begum, Noorzahan; Ferdousi, Sultana; Begum, Selina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Hyperthyroidism is associated with altered cardiac autonomic nervous activity (CANA). Heart Rate Variability (HRV) analysis is a promising technique to quantify CANA and therefore can be done in hyperthyroidism. Objective: To observe the HRV parameters in patients with hyperthyroidism to find out the influence of excess thyroid hormone on cardiac autonomic nervous activities. Method: The cross sectional study was carried out on 60 hyperthyroid patients (groupB) aged 30-50 years in the Department of Physiology, BSMMU, Dhaka from 1st July 2007 to 30th June 2008. Age and sex matched 20 apparently healthy euthyroids were also studied for comparison (group A). On the basis of treatment, they were further divided into group B1 consisting of 30 untreated newly diagnosed patients and group B2 consisting of 30 hyperthyroid patients treated with antithyroid drugs for at least 2 months. The patients were selected from the Out Patient Department of Endocrinology, BSMMU, Dhaka. To assess thyroid status, serum TSH and serum FT4 levels were measured by AxSym system and time domain measures of HRV such as mean R-R interval, mean heart rate, SDNN and RMSSD were assessed from 5 minute (short term) ECG recording by a polygraph. For statistical analysis Mann-Whitney U test was done. Results: Mean R-R interval was significantly (P<0.001) lower but mean heart rate was significantly (P<0.001) higher in untreated patients than those of treated and euthyroids subjects. These values were found almost similar when compared between euthyroids and treated hyperthyroids. Similarly SDNN and RMSSD were significantly lower in untreated hyperthyroids than both euthyroids (P<0.001) and treated hyperthyroids (P<0.01). Conclusion: This study concluded that decreased vagal modulation on heart rate may occur in hyperthyroidism, which may be restored following adequate treatment of the disease. Keywords: HRV, R-R Interval, Heart rate, RMSSD, Hyperthyrodism DOI: 10.3329/jbsp.v4i2.4172 J Bangladesh Soc Physiol. 2009 Dec;4(2): 51-57